Identification of Factors Influencing the Use of QRIS Using TAM and UTAUT 2 Methods - Nuswantoro, Setio Ardy; Muhammad Ulfi; Miftahurrizqi; Muhammad Rafli (Universitas Negeri Semarang, 2024)
Purpose: This research aims to analyze user behavior towards Quick Response Code Indonesian Standard (QRIS) usage, employing the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) and Technology Acceptance Model (TAM) methods. Methods: Online surveys were conducted among QRIS users, focusing on factors influencing adoption intention and usage behavior in Indonesian society. Sampling was random, with a sample size determined for a 95% confidence level and 5% margin of error. Data analysis employed Confirmatory Factor Analysis (CFA) for validity and reliability testing, followed by Structural Equation Modeling (SEM) to assess model fit. Result: The research results indicate the validity and reliability of the structural model, with Performance Expectancy significantly impacted by Effort Expectancy. However, Effort Expectancy insignificantly affects Behavioral Intention and Use Behavior, consistent with previous research. But when Effort Expectancy and Performance are used as mediating variables between Perceived Trust and Behavioral Intention, they have a significant impact on this relationship. Social Influence also insignificantly affects Behavioral Intention and Use Behavior. Facilitating Condition, Perceived Trust, Hedonic Motivation, Price Value, and Habit demonstrate significant impacts on Behavioral Intention and Use Behavior, reaffirming prior findings. Some variables also have a big influence on other variables, such as Perceived Trust has major impact to Effort Expectancy, and Habit which has a major impact on Behavioral Intention and Use Behavior as a whole. Additionally, Behavioral Intention significantly affects Use Behavior. Novelty: Effort Expectancy insignificantly affects Behavioral Intention and Use Behavior. However, when Effort Expectancy and Performance are used as mediating variables between Perceived Trust and Behavioral Intention, they have a significant impact on this relationship. Some variables also have a big influence on other variables, such as Perceived Trust has major impact to Effort Expectancy, and Habit which has a major impact on Behavioral Intention and Use Behavior as a whole. This study contributes to understanding QRIS adoption and usage behavior, offering insights for policymakers and practitioners in the digital payment sector.